Optimal power flow in the presence of wind power using modified cuckoo search - Mishra C.; Singh S.P.; Rokadia J. (My University, 2025)
This study proposes a solution to the optimal power flow (OPF) in power systems incorporating wind power. The wind generated electricity's cost modelling is presented which owes to the stochastic nature of wind speed based on the Weibull probability density function. The wind associated costs comprise of (i) reserve cost arising out of overestimation of wind farm output and (ii) penalty cost for not using total available wind power which are included in the conventional OPF. Furthermore, the Q-V formulation of induction generator is deduced which is incorporated through a modification in the conventional load flow solution. A modified cuckoo search optimisation technique is employed and compared with modified particle swarm optimisation for solving OPF with wind power involved. A modified IEEE 30-bus and IEEE 57-bus systems are used as test systems and it is observed that the cuckoo search performs better than particle swarm optimisation. © The Institution of Engineering and Technology.